2013
DOI: 10.1016/j.physa.2013.07.063
|View full text |Cite
|
Sign up to set email alerts
|

Network structure of inter-industry flows

Abstract: We study the structure of inter-industry relationships using networks of money flows between industries in 20 national economies. We find these networks vary around a typical structure characterized by a Weibull link weight distribution, exponential industry size distribution, and a common community structure. The community structure is hierarchical, with the top level of the hierarchy comprising five industry communities: food industries, chemical industries, manufacturing industries, service industries, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 39 publications
(42 reference statements)
1
68
2
Order By: Relevance
“…In fact, J. McNerney et al (1995) analyzed the Korean IO table classified into 39 industries and reported that the completeness(density) was 0.888, which is much higher than the results of this study [4]. …”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…In fact, J. McNerney et al (1995) analyzed the Korean IO table classified into 39 industries and reported that the completeness(density) was 0.888, which is much higher than the results of this study [4]. …”
Section: Resultscontrasting
confidence: 73%
“…In network theory, centralities such as degree centrality, closeness centrality, and betweenness centrality have been used. J. McNerney et al have defined nodes with large in-flow (that is, out-flow) as important nodes [4]. D. Aobdia et al used eigenvector centrality to find central industries in inter-industry networks [2], and reported that the accounting performance of the central industries is more closely related to macroeconomic indicators than noncentral industries is and better explains the performance of the surrounding industries.…”
Section: Introductionmentioning
confidence: 99%
“…Also, McNerney and Fath (2013) have previously applied information theory and other network metrics to I-O matrices of multiple countries. However, McNerney and Fath (2013) were limited to either one or two years of I-O tables for any given country.…”
Section: Economic Structure Perspectivementioning
confidence: 99%
“…That is to say I performed no computational analysis, such as clustering (McNerney et al 2013), to group the economic sectors. To explore the implications of the size of the network (e.g., the number of sectors) on the calculations in this paper, I also reduce the I-O tables to 12, 7, and 2 sector versions and report on the trends (see ''Information Theory Trends as a function of Network Size'' section for results and Tables S1 and S2 for sector descriptions).…”
Section: I-o Data and Harmonizationmentioning
confidence: 99%
“…Such a research avenue has been boosted by a rising number of papers exploring the structure and consequences of economics networks, including trade (Fagiolo et al, 2009), production (Hausmann andHidalgo, 2011), input-output interdependencies (McNerney et al, 2012) and finance (May et al, 2008, Haldane and May, 2011, NP, 2013. Furthermore, in the last years, the topics of international migration and human temporary mobility have received an increased attention in the field of network science, for their straightforward connections with crucial large-scale phenomena like global-epidemic spreading (Balcan et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%